2013
DOI: 10.1007/s11468-013-9660-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Enhanced Fluorescence Biosensors: a Review

Abstract: Surfaces of metallic films and metallic nanoparticles can strongly confine electromagnetic field through its coupling to propagating or localized surface plasmons. This interaction is associated with large enhancement of the field intensity and local optical density of states which provides means to increase excitation rate, raise quantum yield, and control far field angular distribution of fluorescence light emitted by organic dyes and quantum dots. Such emitters are commonly used as labels in assays for dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
396
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 415 publications
(399 citation statements)
references
References 137 publications
(169 reference statements)
1
396
1
1
Order By: Relevance
“…Largely enhancement of the local electromagnetic (EM) field induced by surface plasmon resonance (SPR), which plays an important role in studying SES, including PEF and surface-enhanced Raman scattering (SERS), have the focus of discussions [10][11][12][13]. It is found that the characteristic of SPR (position and intensity) are critically dependent upon the geometrical parameter of the nanostructures, such as the size, shape, as well as the the composition of the nanostructure, and the dielectric constant of the surrounding environment [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Largely enhancement of the local electromagnetic (EM) field induced by surface plasmon resonance (SPR), which plays an important role in studying SES, including PEF and surface-enhanced Raman scattering (SERS), have the focus of discussions [10][11][12][13]. It is found that the characteristic of SPR (position and intensity) are critically dependent upon the geometrical parameter of the nanostructures, such as the size, shape, as well as the the composition of the nanostructure, and the dielectric constant of the surrounding environment [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, better understanding of coupling and interconversion mechanism among free electrons, surface plasmon, photons, and fluorophores based on metal substrate with various shape configurations in PEF effect still should be highlighted [10,11,20]. In this review, we focus on the recent advancement of the effect of plasmonic nanostructures towards PEF.…”
Section: Introductionmentioning
confidence: 99%
“…1 This phenomenon has been demonstrated by tremendous applications on chemical and biological sensors. [2][3][4][5][6] Highly enhanced local electromagnetic fields created by the resonantly pumped plasmonic nanostructures result in greatly increased incident light absorption and enhanced emitter excitation, supporting surface-enhanced spectroscopies including surface-enhanced Raman scattering, 7,8 surface-enhanced infrared spectroscopy, [9][10][11] and surface plasmon-enhanced fluorescence (SPFS). [12][13][14] Surface plasmons (SPs) with field E SP excited by an incoming light E 0 can enhance fluorophore excitation rate and Raman scattering by factors up to |E sp /E 0 | 2 and |E sp /E 0 | 4 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmons can be excited by exposing subwavelength conductive particles to an external electromagnetic field, resulting in localized plasmon-polaritons (LPP) or by coupling the external field to the oscillating charges near the surface of the material, resulting in a highly confined surface wave propagating along the interface between the conductive and dielectric media, known as surface plasmon-polaritons (SPP) [1]. High confinement of this enhanced field provides higher local optical density of states and leads to applications such as plasmonenhanced photovoltaics [2], biosensing [3], Raman spectroscopy [4] and photocatalysis [5]. Furthermore, SPP's enable subwavelength spatial confinement of light, due to their dispersion properties.…”
Section: Introductionmentioning
confidence: 99%